A Hybrid Algorithm for the Computation of Fixed Points - Garcia, C. B. (Management Science, 1976)
Given a continuous mapping of a simplex to itself, an algorithm is shown that generates an infinite sequence of points converging to a fixed point of the mapping. Taking advantage of a generalization of Sperners lemma, the proposed method generalizes those of Scarf and Eaves in a manner such that both methods are given a unifying formulation.